Cats of Any Color : Jazz Black and White. (Oxford University Press, USA, 1995)
It was none other than Louis Armstrong who said, 'These people who make the restrictions, they don't know nothing about music. It's no crime for cats of any colour to get together and blow.' In Cats of Any Color, Gene Lees takes a long overdue look at the shocking pervasiveness of racism in jazz's past and present - both the white racism that long ghettoized the music and generations of talented black musicians, and what Lees maintains is an increasingly virulent reverse racism aimed at white jazz musicians. In candid interviews, living jazz legends such as Horace Silver, Red Rodney (Charlie Parker's white trumpet player), and Dave Brubeck (part Modoc Indian), step forward and share their thoughts on how racism has affected their lives. At the heart of this book is a passionate plea to recognize jazz not as the sole property of any one group, but as an art form celebrating the human spirit.